Corporate pension plans and investment choices: Bargaining or conforming? - Duygun, Meryem; Huang, Bihong; Qian, Xiaolin; Tam, Lewis H.K. (Journal of Corporate Finance, 2018)
This paper investigates the impacts of defined-benefit (DB) pension plans on the corporate investment choices between diversifying and non-diversifying investments. We find a firm's DB plan coverage is negatively associated with its propensity of making a major investment. Subject to a major investment decision, however, the firms with higher DB plan coverage is more likely to diversify, i.e. acquire firms abroad or in other industries, rather than invest in fixed assets or make non-diversifying (i.e. domestic horizontal) acquisitions. Moreover, in diversifying acquisitions, they are more likely to invest in countries or industries with strongly unionized workforce. Further analysis on post-investment performance shows that firms with higher DB plan coverage experience a greater improvement in operating profitability after a diversifying acquisition, and the improvement mainly comes from a higher asset turnover rather than cost reduction. On the other hand, DB plan sponsoring firms experience a decline in profitability after a large capital expenditure or a non-diversifying acquisition. We propose both bargaining motive and conforming motive can explain these results.